A Particle-Scale Model of Surface Tension for Two-Phase Flow: Model Description and Validation - Xiaoxi Zhang; Can Cao; Nan Gui; Xiaoli Huang; Xingtuan Yang; Jiyuan Tu; Shengyao Jiang; Qian Zhao (Energies, 2022)
A particle-scale surface tension force model (STF) is proposed here to be incorporated in the smoothed hydrodynamics particle (SPH) method. This model is based on the identification of interface geometry and the gradient of densities across the interface. A square bubble of single-phase and a square bubble immersed in fluids are simulated by the STF model accompanied with a combined kernel in SPH to validate their suitability to simulate the immersed bubble motion. Two cases of rising bubbles, i.e., a single rising bubble and a pair of rising bubbles, are simulated for demonstration. The rising velocity, density, surface tension force, interfacial curvature, the power of the STF, and the smoothing length of the rising bubble and surrounding fluids are all computed by the current STF model to study the characteristics of immersed bubble’s motion and coalescence. The current model provides a way to capture the interfacial interactions in two-phase flows at particle scales.